The Domination of Divorce by Litigation Cases; Factors and Implications (a Case Study of Parepare Religious Court Class IB) - M. Arafah; Qadir Gassing; Rahmatiah HL; Nasruddin Khalil Hrp (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
Divorce is a phenomenon of family division involving husband and wife with an increasing percentage in Indonesia. The increase in divorce cases in court is due to the insistence on divorce by litigation and divorce by talaq as the main initiative of husband and wife at the Parepare Religious Court. In order to discuss these issues, the data was collected using a field research (qualitative descriptive) system, so that the results showed that divorce cases from 2019-2020 showed that divorce by litigation was more dominant than divorce by talaq at the Parepare Religious Courts Class 1B. The presentation of the increasing number of divorces by litigation indicated that the wives were dissatisfied with the duties and obligations of their husbands in their marital life. Meanwhile, the factors that influenced divorce by litigation at the Parepare Religious Court consisted of 13 factors, namely third parties, drunkenness, mandates, gambling, leaving one party, imprisoned, polygamy, Domestic Violence (DV), disability, disputes or quarrels continuously, forced marriage, apostasy, and economics. In reality, economic problems, leaving one party and disputes or quarrels continuously were the highest causes in the 2019-2020 timeframe. As a result, divorce cases affected the children's psychology and the disharmony of each party